Familial amyloidotic polyneuropathy without familial occurrence: carrier detection by the radioimmunoassay of variant transthyretin. Issue 4 (April 1988) - Tanaka, M; Hirai, S; Matsubara, E; Okamoto, K; Morimatsu, M; Nakazato, M
Abstract : A 47 year old woman with familial amyloidotic polyneuropathy (FAP) is reported, without familial occurrence of the disease. Her 81 year old mother and 53 year old sister were proved to be asymptomatic carriers for variant transthyretin (TTR) by means of the radioimmunoassay. It is suggested that unknown factor(s) may play a role in preventing or delaying the onset of the disease, producing variations in sex and family incidence. In order to establish the diagnosis of non-hereditary primary amyloidotic polyneuropathy, it must be confirmed that variant TTR is absent in the serum of relatives.